Unexpected reversible and controllable nuclear uptake and efflux of the DNA "light-switching" Ru(ii)-polypyridyl complex in living cells via ion-pairing with chlorophenolate counter-anions. Issue 45 (10th November 2020) - Huang, Rong; Zhu, Jian-Qiang; Tang, Miao; Huang, Chun-Hua; Zhang, Zhi-Hui; Sheng, Zhi-Guo; Liu, Sijin; Zhu, Ben-Zhan
Abstract : An in-depth understanding of the mechanisms of cellular uptake and efflux would facilitate the design of metal complexes with not only better functionality and targeted theranostic efficiency, but also with controlled toxicity. Abstract : An in-depth understanding of the mechanisms of cellular uptake and efflux would facilitate the design of metal complexes with not only better functionality and targeted theranostic efficiency, but also with controlled toxicity. Here we find, unexpectedly, that the DNA "light-switching" Ru(ii )-polypyridyl complex [Ru(phen)2 (dppz)] 2+ already delivered to the nucleus via ion-pairing with chlorophenolate counter-anions can gradually efflux to the cytoplasm when the cells were washed and incubated with fresh culture-medium. Interestingly, [Ru(phen)2 (dppz)] 2+ effluxed to the cytoplasm can be redirected back to the nucleus when the chlorophenolate counter-anions were added again. The efflux of nuclear [Ru(phen)2 (dppz)] 2+ was found to be mediated mainly via ATP-binding cassette (ABC) transporter proteins. Analogous reversible, but enantio-selective nuclear uptake and efflux were observed with the two pure chiral forms of [Ru(phen)2 (dppz)]Cl2 . This represents the first report of reversible and controllable nuclear uptake and efflux of a DNA "light-switching" Ru(ii )-complex in living-cells via ion-pairing, which should provide novel insights for future research on using ion-pairing as an effective approach to control the cellular uptake and redistribution of other potential theranostic metal complexes.